Effect of Whole Body Vibration Training during the Recovery Time on the Anaerobic Performance Indices and the Blood Lactate Concentration of Men Wrestlers - Sajad Arshadi; Mehdi Noora; Rodabeh Shakibatabar (Islamic Azad University, 2018)
Introduction: Whole body vibration (WBV) has been studied as a relatively new and effective way to provide strong mechanical stimulation in the muscular nervous system, cardiovascular, respiration, bone and muscle tissue in a wide range of medical, ergonomic and animal experiments. This study aimed to investigate the effect of WBV during the recovery period on the anaerobic performance indices and the blood lactate concentration of wrestlers. Methods: Twelve male wrestlers of college students in Tehran with a mean age of 25.75 ± 2.55 years old, height 175.58 ± 6.35 cm, weight 71.4 ± 7.75 kg and body fat percentage 14.22 ± 6.87 (%) volunteered for participation in the study. The training protocol was 10 minutes of warming and then the subjects performed intensive anaerobic activity for 2 minutes and then 15 minutes of recovery was performed; after a recovery, the same 2 minutes of intensive anaerobic activity was repeated. On the first day, inactive recovery, and after four days on the second day, WBV as active recovery was used. In this study, blood lactate concentrations were measured four times. Paired sample t-test, repeated measure ANOVA and Bonferroni post hoc at significant level of 0.05 were used to analyze the data. Results: The results of present study showed that WBV in comparison with inactive recovery, improves the anaerobic power of wrestlers in the second activity than the first activity (Peak Power, p=0.61; Average Power, p=0.62), but does not have a significant effect on the concentration of blood lactate (p=0.006). Conclusion: This study showed WBV as an active recovery method can have beneficial effects on the improvement of anaerobic power indices and blood lactate in wrestlers.